Analysis of a Series of 26 Cases With Prenatal Skeletal Dysplasia via Multiplatform Genetic Detection - Li‐min Cui; Hua‐ying Hu; Xiao‐mei Zhai; Ming‐fei Qi; Yan‐ming Liu; Cong‐ying Han; Jing Zhang; Ming Shen; Yu‐lan Xiang; Wen‐qi Chen; Kai Yang; Dong‐liang Zhang; et al. (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Skeletal dysplasia (SD) represents a series of highly heterogeneous congenital genetic diseases affecting the human skeletal system. Refined genetic diagnosis is helpful for the accurate diagnosis and prognosis evaluation of SDs. Materials and Methods In this study, we recruited 26 cases of SD and analyzed them with a designed sequential genetic detection. Chromosome karyotyping, microarray analysis (CMA), and whole exome sequencing (WES) techniques are performed as needed. Sanger sequencing and fluorescent quantitative PCR (QF‐PCR) were used as validation methods. Results A total of 16 cases (61.5%, 16/26) received positive results at various levels of testing, including one trisomy 18, four copy number variations (CNVs), and 11 sequence variations. Additionally, four novel SD‐related sequence mutations were detected in this study. Conclusion Our findings provide conclusive evidence for genetic counseling of corresponding families and expand the mutation spectrum of SD. In addition, this study demonstrates that a strategy sequentially including various genetic techniques contributes to the diagnosis of highly heterogeneous genetic disorders such as SD.